A nursing smoking cessation package for nicotine dependence: An innovative care approach for smokers with non - communicable diseases - Punpakdee, Orasa; Suteerangkul, Peeraya; Kalampakorn, Surintorn (Thai Journal of Nursing, 2026)
Patients with chronic non-communicable diseases (NCDs) who smoke, should be encouraged to quit smoking because tobacco use adversely affects disease control, leading to accelerated the development of complications, increasing disease severity, resulting in premature death. Nurses could have the opportunity to assist patients in quitting smoking; however, due to time constraints and confidence in helping patients quit, a nursing smoking cessation package for nicotine dependence has been developed as an innovative nursing practice. This package provides nurses with motivational conversation scripts that can be used as examples for delivering brief advice and brief counselling tailored to patients at different stages of readiness to quit smoking. In addition, the package includes support materials to facilitate smoking cessation, such as information brochures, a self-help booklet, a self- monitoring record, and herbal remedies to help alleviate cravings. A smoking cessation follow- up quit is also included for use on a patient’s follow up sheet. Nurses can use this innovation package in their routine care for patients at NCD clinics to support smoking cessation within a limited amount of advice time.